2019
DOI: 10.1186/s12905-019-0776-4
|View full text |Cite
|
Sign up to set email alerts
|

Short birth interval and associated factors among women of child bearing age in northern Ethiopia, 2016

Abstract: Background Short birth interval is known to have a negative effect on perinatal, neonatal and child health outcomes. In Ethiopia, 29% of births are short birth intervals at less than 24 months. Even though optimum birth spacing is considered as an essential factor for the health of women and their children, to the best of the authors’ knowledge studies conducted on short birth interval are insufficient to inform policy makers. Therefore, the aim of this study was to assess short birth interval and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
66
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(90 citation statements)
references
References 18 publications
12
66
6
Order By: Relevance
“…This study revealed that as breastfeeding duration of the index child increase by one month, the odds of SBI among childbearing women decrease by 79%. This finding is similar to a study done in Serbo Town, Southwest Ethiopia [16], a systematic review of 58 observational studies [49], Northern Ethiopia [14], Dodota district, Southern Ethiopia [24], Northern Ethiopia [50], and Egypt [54]. Optimal breastfeeding prolongs the length of time between two consecutive births.…”
Section: Plos Onesupporting
confidence: 90%
See 4 more Smart Citations
“…This study revealed that as breastfeeding duration of the index child increase by one month, the odds of SBI among childbearing women decrease by 79%. This finding is similar to a study done in Serbo Town, Southwest Ethiopia [16], a systematic review of 58 observational studies [49], Northern Ethiopia [14], Dodota district, Southern Ethiopia [24], Northern Ethiopia [50], and Egypt [54]. Optimal breastfeeding prolongs the length of time between two consecutive births.…”
Section: Plos Onesupporting
confidence: 90%
“…For instance, the majority of the community in the four developing regions of Ethiopia are Muslim religious faith followers, in which the use of modern contraceptives for child spacing does not have been practiced yet [52]. This finding is also consistent with a study conducted in Northern Ethiopia [14], Jimma Zone, Southwest Ethiopia [15], rural developing communities of Southern Ethiopia [17] and Kassala, Eastern Sudan [53]. Furthermore, the lifestyle of the community in the developing regions is purely dependent on livestock, in which having more children is considered as advantageous to get more keeper for their cattle.…”
Section: Plos Onesupporting
confidence: 86%
See 3 more Smart Citations